The influence of Land Quality on Productivity of Maize in Soils Derived from Volcanic and Sedimentary Rocks in the Bogor Area - DJADJA SUBARDJA; . SUDARSONO (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2005)
Land quality has a good relationship with the productivity of maize which is influenced by parent materials and soil development, especially the nutrient retention and aluminum toxicity. Nutrient availability is strongly influenced by land management. On the intensively land use and continuously fertilizer applied is showing a high content of available P at top soil and give a high yielding of maize. Result of land evaluation in the study area by using the existing criteria of land suitability of maize indicated the same class of land suitability of S3 and therefore not suited to the field condition. The main limitation was a nutrient retention (i.e. pH, base saturation). Nutrition availability of available P and toxicity of aluminum are excluded in the criteria. Land suitability criteria of maize were built by relevant land qualities and productivity of maize gave more realistic and quantitative results of land suitability of the area. The most influenced of land quality to the maize productivity are nutrient availability, nutrient retention and aluminum toxicity by mean of land characteristics of available P, pH and exchangeable Al. A few data required for land evaluation and therefore it will be easily to be processed, faster, efficient and accurately. Application of the P fertilizer and liming are strongly recommended for the area, especially on the acid soils of sedimentary rock to increase the productivity of maize.